Exercise training intensity determination in cardiovascular rehabilitation: Should the guidelines be reconsidered?. (29th August 2020) - Hansen, Dominique; Bonné, Kim; Alders, Toon; Hermans, Ann; Copermans, Katrien; Swinnen, Hans; Maris, Vincent; Jansegers, Thomas; Mathijs, Wout; Haenen, Laura; Vaes, Johan; Govaerts, Emmanuela; et al.
Abstract: Aims: In the rehabilitation of cardiovascular disease patients a correct determination of the endurance-type exercise intensity is important to generate health benefits and preserve medical safety. It remains to be assessed whether the guideline-based exercise intensity domains are internally consistent and agree with physiological responses to exercise in cardiovascular disease patients. Methods: A total of 272 cardiovascular disease patients without pacemaker executed a maximal cardiopulmonary exercise test on bike (peak respiratory gas exchange ratio >1.09), to assess peak heart rate (HRpeak ), oxygen uptake (VO2peak ) and cycling power output (Wpeak ). The first and second ventilatory threshold (VT1 and VT2, respectively) was determined and extrapolated to %VO2peak, %HRpeak, %heart rate reserve (%HRR) and %Wpeak for comparison with guideline-based exercise intensity domains. Results: VT1 was noted at 62 ± 10% VO2peak, 75 ± 10% HRpeak, 42 ± 14% HRR and 47 ± 11% Wpeak, corresponding to the high intensity exercise domain (for %VO2peak and %HRpeak ) or low intensity exercise domain (for %Wpeak and %HRR). VT2 was noted at 84 ± 9% VO2peak, 88 ± 8% HRpeak, 74 ± 15% HRR and 76 ± 11% Wpeak, corresponding to the high intensity exercise domain (for %HRR and %Wpeak ) or very hard exercise domain (for %HRpeak and %VO2peak ). At best (when using %Wpeak ) in only 63% and 72% of all patients VT1 and VT2, respectively, corresponded to the same guideline-based exercise intensity domain, but this dropped to about 48% and 52% at worst (when using %HRR and %HRpeak, respectively). In particular, the patient's VO2peak related to differently elicited guideline-based exercise intensity domains ( P  < 0.05). Conclusion: The guideline-based exercise intensity domains for cardiovascular disease patients seem inconsistent, thus reiterating the need for adjustment.